Dioxygen activation and pyrrole α-cleavage with calix(4)pyrrolato aluminates: enzyme model by structural constraint - Sigmund, Lukas M.; Ehlert, Christopher; Enders, Markus; Graf, Jürgen; Gryn’ova, Ganna; Greb, Lutz (Angewandte Chemie. International edition, 2021)
The present work describes the reaction of triplet dioxygen with the porphyrinogenic calix[4]pyrrolato aluminates to alkylperoxido aluminates in high selectivity. Multiconfigurational quantum chemical computations disclose the mechanism for this spin-forbidden process. Despite a negligible spin-orbit coupling constant, the intersystem crossing (ISC) is facilitated by singlet and triplet state degeneracy and spin-vibronic coupling. The formed peroxides are stable toward external substrates but undergo an unprecedented oxidative pyrrole α-cleavage by ligand aromatization/dearomatization-initiated O−O σ-bond scission. A detailed comparison of the calix[4]pyrrolato aluminates with dioxygen-related enzymology provides insights into the ISC of metal- or cofactor-free enzymes. It substantiates the importance of structural constraint and element-ligand cooperativity for the functions of aerobic life.
First published: 06 May 2021
Gesehen am 29.11.2022